Exploring the Sustainable Development Strategy of Ancient Towns in Southern Jiangsu Driven by the Homogeneity of Tourism Towns - Yu, Yuting (Transactions on Social Science, Education and Humanities Research, 2023)
In recent years, local governments have excessively interfered with the development and construction of ancient towns in southern Jiangsu, replacing planning with planning, without considering local conditions and only focusing on economic benefits and political achievements. Local governments have blindly built some high return value projects, leading to the homogenization of tourist ancient towns in various regions. How to effectively coordinate the contradiction between the protection of ancient towns and tourism development has become an urgent focus of attention. This article attempts to explore the sustainable development strategies of ancient towns in southern Jiangsu under the drive of homogenization of tourism towns. Comprehensively combine the internal resources of the ancient town in southern Jiangsu to form a unique style, gradually build and open related tourism projects, and after the overall construction is completed, launch a new image to avoid hardware being unable to keep up with the software situation. The sustainable development of tourism in ancient towns requires scientific and professional planning in order to effectively avoid any possible damage to the town. The tourism development planning of ancient towns should not be blindly carried out and rushed forward. The feasibility of tourism development should be evaluated and carried out in stages and batches. Improving the cultural quality of local residents and gaining their support is the key to achieving sustainable resource development.